2020
DOI: 10.3390/ijgi9060370
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Ensemble Object Detection with Optimized Coefficients for Remote Sensing Images

Abstract: The detection of objects in very high-resolution (VHR) remote sensing images has become increasingly popular with the enhancement of remote sensing technologies. High-resolution images from aircrafts or satellites contain highly detailed and mixed backgrounds that decrease the success of object detection in remote sensing images. In this study, a model that performs weighted ensemble object detection using optimized coefficients is proposed. This model uses the outputs of three different object detection model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Many ensemble methods [ 35 , 36 ], therefore, seek to promote diversity among their combined models. More recent studies have shown the effectiveness of ensemble methods in both classification [ 37 , 38 ] and object detection [ 39 , 40 ] problems. However, the process to ensemble object detectors is costly in time and memory both at training and inference, which limits its applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Many ensemble methods [ 35 , 36 ], therefore, seek to promote diversity among their combined models. More recent studies have shown the effectiveness of ensemble methods in both classification [ 37 , 38 ] and object detection [ 39 , 40 ] problems. However, the process to ensemble object detectors is costly in time and memory both at training and inference, which limits its applicability.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used augmentation approach in remote sensing is also color and geometrical transformations [45], [49], [19], [16]. In [21], rescaling, slicing, and rotation augmentations were applied in order to increase the quantity and diversity of training samples in building semantic segmentation task.…”
Section: Related Workmentioning
confidence: 99%
“…The considered in our study transformations are described in Table 1. Since most of the works in remote sensing do not specify albumentations parameters for images augmentation [49], [19], we also set default parameters.…”
Section: Object-based Augmentationmentioning
confidence: 99%
“…The training of SSD was done using ResNet-152 architecture [41] from Torchvision version 0.3.0 [42]. [35] and [43]. The full parameters and layers of the SSD model that we used are available in Appendix A.…”
Section: Preparing the Training And Validation Datamentioning
confidence: 99%
“…The f1-Score (Equation (3)) was used to assess the performance of species classification; therefore, it was only computed for sites 1 and 2, where species information was available. Due to the class imbalance [35] and [43]. The full parameters and layers of the SSD model that we used are available in Appendix A.…”
Section: Detecting With Single Modelsmentioning
confidence: 99%